(untitled) (American International Journal of Humanities, Arts and Social Sciences, 2019)
The purpose of this study was to find the level of orphans’ motivation for higher education and factors contributing their motivation for higher education. Since Kandahar is one of the historically and strategically important provinces of Afghanistan in which four-decade war have adversely affected different aspects of lives of its population. Orphan and education seem two contradictory terms in a country like Afghanistan with four-decade war history. The study is descriptive in nature where a quantitative questionnaire was designed to collect data from randomly selected 112 students studying in 10th, 11th and 12th of Shaikh Zaid orphanage and from 15 graduates through snowball sampling method. The findings revealed that orphans are motivated for higher education transportation, financial problem, daydreaming, distraction during study are the major challenges that prevent orphans from getting higher education.